2016
DOI: 10.3389/fmicb.2016.01334
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Rhizospheric Actinomycetes for Various In-vitro and In-vivo Plant Growth Promoting (PGP) Traits and for Agroactive Compounds

Abstract: In this study 98 rhizospheric actinomycetes were isolated from different wheat and tomato fields, Punjab, Pakistan. The isolates were characterized morphologically, biochemically, and genetically and were subjected to a comprehensive in vitro screening for various plant growth promoting (PGP) traits. About 30% of the isolates screened were found to be the promising PGP rhizobacteria (PGPRs), which exhibited maximum genetic similarity (up to 98–99%) with different species of the genus Streptomyces by using16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
107
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(118 citation statements)
references
References 42 publications
6
107
1
4
Order By: Relevance
“…It is established well that plant associated-bacteria lowers the ethylene levels of plants through the ACC deaminase activity and helps to grow under biotic and abiotic stresses [61]. In this study, all the strains were found positive for ACC deaminase, but it was lower than previous reports of ACC-D production by Pseudomonas fluorescens and Streptomyces djakartensis TB4 [61][62][63].…”
Section: Discussioncontrasting
confidence: 45%
“…It is established well that plant associated-bacteria lowers the ethylene levels of plants through the ACC deaminase activity and helps to grow under biotic and abiotic stresses [61]. In this study, all the strains were found positive for ACC deaminase, but it was lower than previous reports of ACC-D production by Pseudomonas fluorescens and Streptomyces djakartensis TB4 [61][62][63].…”
Section: Discussioncontrasting
confidence: 45%
“…ACC can be converted into ammonia and a-ketobutyrate (Honma and Shimomura 1978) by the enzyme ACC deaminase that bring down plant ethylene levels. Streptomyces are reported to possess ACC deaminase activity (Wang et al 2000;Ali et al 2012) and can help to reduce pathogen related plant stress (Munees and Mulugeta 2014;Anwar et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the previous study by Kaur et al (2017) reported that 16 isolates of Actinomycetes isolated from the rhizosphere of Gladiolus were able to produce IAA with concentrations ranging from 8.1 to 79.9 ppm. Anwar et al (2016) also reported that 30 Actinomycetes isolated from the rhizosphere of wheat and tomatoes were able to produce IAA with concentrations ranging from 10-79.5 ppm. The results of this study indicated that the most Actinomycetes isolated from the rhizosphere of maize were able to produce IAA.…”
Section: Discussionmentioning
confidence: 97%